Dimethylarginine dimethylaminohydrolase 1 deficiency aggravates monocrotaline-induced pulmonary oxidative stress, pulmonary arterial hypertension and right heart failure in rats. (15th November 2019) - Wang, Dongzhi; Li, Hailing; Weir, E. Kenneth; Xu, Yawei; Xu, Dachun; Chen, Yingjie
Abstract: Patients with pulmonary arterial hypertension (PAH) and right ventricular (RV) failure have a poor clinical outcome, but the mechanisms of PAH and RV failure development are not totally clear. PAH is associated with reduced NO bioavailability and increased endogenous NOS inhibitor asymmetric dimethylarginine (ADMA). Dimethylarginine dimethylaminohydrolase-1 (DDAH1) plays a critical role in ADMA degradation. Here we generated a novel DDAH1 deficiency rat strain using the CRISPR-Cas9 technique, and studied the effect of DDAH1 dysfunction on monocrotaline-induced PAH, lung vascular remodeling and RV hypertrophy. DDAH1 knockout resulted in abolished DDAH1 expression in various tissues, and significant increases of plasma and lung ADMA content. DDAH1 knockout has no detectable effect on cardiac and lung structure, and LV function under control conditions in rats. However, DDAH1 knockout significantly aggravated monocrotaline-induced lung and RV oxidative stress, lung vascular remodeling and fibrosis, pulmonary hypertension and RV hypertrophy in rats. DDAH1 KO resulted in significantly greater increases of plasma and lung ADMA content under control conditions. In the wild type rats monocrotaline resulted in significant increases of plasma and lung ADMA contents and reduction of lung eNOS protein content and these changes were more marked in DDAH1 KO rats. Together, our results demonstrated that DDAH1 plays an important role in attenuating monocrotaline-induced lung oxidative stress, pulmonary hypertension and RV hypertrophy in rats. Highlights: DDAH1 deficiency results in increase of blood and tissue ADMA in rats. DDAH1 knockout does not cause spontaneous pulmonary hypertension in rats. DDAH1 knockout exacerbated MCT-induced decrease of lung NO production in rats. DDAH1 attenuates MCT-induced lung remodeling and pulmonary hypertension in rats. DDAH1 attenuates MCT-induced RV oxidative stress, hypertrophy and failure in rats.